2023
DOI: 10.1111/vco.12920
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stereotactic radiation therapy for the treatment of confirmed or presumed canine glioma

Erin Trageser,
Tiffany Martin,
Braden Burdekin
et al.

Abstract: Intracranial gliomas are the second most common brain tumour in dogs. Radiation therapy provides a minimally invasive treatment option for this tumour type. Earlier publications reporting on the use of non‐modulated radiation therapy suggested a poor prognosis for dogs with glioma, with median survival times ranging between 4 and 6 months; more recent literature utilizing stereotactic radiation therapy (SRT) demonstrates that the prognosis for canine gliomas may be more promising, with survival times closer to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Surgical treatment of gliomas is infrequently attempted as approaching and removing them is technically demanding due to their intra-axial location [ 6 , 28 ]. Radiation therapy (RT): it has been shown to be beneficial for the treatment of intracranial tumours used as a monotherapy or adjunctive modality [ 11 , 12 , 13 , 22 , 31 , 32 , 33 ]. Although meningiomas are associated in the literature with a significantly better prognosis in terms of survival compared to gliomas, recent studies reported similar survival times in both types of tumours [ 33 , 34 ].…”
Section: Brain Diseasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Surgical treatment of gliomas is infrequently attempted as approaching and removing them is technically demanding due to their intra-axial location [ 6 , 28 ]. Radiation therapy (RT): it has been shown to be beneficial for the treatment of intracranial tumours used as a monotherapy or adjunctive modality [ 11 , 12 , 13 , 22 , 31 , 32 , 33 ]. Although meningiomas are associated in the literature with a significantly better prognosis in terms of survival compared to gliomas, recent studies reported similar survival times in both types of tumours [ 33 , 34 ].…”
Section: Brain Diseasesmentioning
confidence: 99%
“… Radiation therapy (RT): it has been shown to be beneficial for the treatment of intracranial tumours used as a monotherapy or adjunctive modality [ 11 , 12 , 13 , 22 , 31 , 32 , 33 ]. Although meningiomas are associated in the literature with a significantly better prognosis in terms of survival compared to gliomas, recent studies reported similar survival times in both types of tumours [ 33 , 34 ]. Another important beneficial effect of radiation therapy is the increase of seizure freedom.…”
Section: Brain Diseasesmentioning
confidence: 99%
See 3 more Smart Citations